2020
DOI: 10.4271/2020-01-0312
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Technique for Measuring Cycle-Resolved Cold Start Emissions Applied to a Gasoline Turbocharged Direct Injection Engine

Abstract: <div class="section abstract"><div class="htmlview paragraph">There is keen interest in understanding the origins of engine-out unburned hydrocarbons emitted during SI engine cold start. This is especially true for the first few firing cycles, which can contribute disproportionately to the total emissions measured over standard drive cycles such as the US Federal Test Procedure (FTP). This study reports on the development of a novel methodology for capturing and quantifying unburned hydrocarbon emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…It has been reported that more than 90% of hydrocarbon (HC) emissions originate from the first 2 min of engine operation when the temperature of the catalysts is low. 2 In the cold start process, the very first firing cycle deserves special attention, as most HCs come out during this cycle, and then gradually decrease during subsequent cycles, as shown by prior cycle-resolved cold start experiments 3,4 by our research team. The fuel rail pressure (FRP) is much lower when the engine is first started during the very first firing cycle, and the cold walls in the engine make the fuel film evaporation very slow, resulting in more fuel injected for compensation and leading to more mixture stratification in the cylinder.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…It has been reported that more than 90% of hydrocarbon (HC) emissions originate from the first 2 min of engine operation when the temperature of the catalysts is low. 2 In the cold start process, the very first firing cycle deserves special attention, as most HCs come out during this cycle, and then gradually decrease during subsequent cycles, as shown by prior cycle-resolved cold start experiments 3,4 by our research team. The fuel rail pressure (FRP) is much lower when the engine is first started during the very first firing cycle, and the cold walls in the engine make the fuel film evaporation very slow, resulting in more fuel injected for compensation and leading to more mixture stratification in the cylinder.…”
Section: Introductionmentioning
confidence: 87%
“…where D is the fractal dimension, which quantitively characterizes the degree of the flame wrinkling; L max is the maximum flame wrinkling scale, which is larger than the integral length scale (L i ), as in equation (3) shown in previous studies, 17,19 or equals the instantaneous flame radius in the early combustion phase when the flame radius is still smaller than L i ; L min is found to be larger than the Kolmogorov length scale (h) in the aforementioned studies, as shown in equation (4).…”
Section: Details Of the Fes Modelmentioning
confidence: 99%
“…All these simulations were carried out using different constant engine speeds. However, as indicated by the cycle-to-cycle experimental measurements in a prior study by our research team, 12 most of the hydrocarbon (HC) emissions originate in the very first firing cycle of the cold start, and then decrease gradually. Therefore, the very first firing cycle should be given special attention.…”
Section: Introductionmentioning
confidence: 89%
“…bag 1 emissions from an FTP-75 test). However, the first 20 s have been identified as the most critical in terms of meeting particulate and gaseous emissions regulations, 10 and studies have focused on the development of fast diagnostics to report time-resolved measurements of emissions 29 instead of or in addition to the total accumulated values.…”
Section: Combustion Modifications To Mitigate Cold-start Disi Emissionsmentioning
confidence: 99%